1985
DOI: 10.1038/318289a0
|View full text |Cite
|
Sign up to set email alerts
|

Specific release of proteoglycans from human natural killer cells during target lysis

Abstract: Natural killer (NK) activity is mediated by a small population of peripheral blood cells that exhibit the homogeneous morphology of large granular lymphocytes (LGL). In recent studies, human NK cell clones have been shown to contain a 200,000-Mr (relative molecular mass) protease-resistant chondroitin sulphate A proteoglycan, which has been localized to the secretory granule by X-ray dispersive analysis and by its resistance to cleavage by extracellular addition of chondroitinase AC or ABC (ref. 7). In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(40 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…Exocytosis of the 35S-labeled proteoglycan from the CNK8 cell was also stimulus specific, being 53% upon incubation with the K562 sensitive target, and 3% for the CEM-resistant target. The correlation of proteoglycan release with target cell susceptibility, coupled with the inhibition of proteoglycan release by monocional antibodies that block JTBI8 and CNK8 cytotoxicity indicates that specific NK effector cell receptors and target cell recognition structures are involved in triggering proteoglycan exocytosis (42). The ability to define one of the granule constituents, proteoglycan, exocytosed from the NK cell via receptor-mediated activation should enable the identification of other granule-associated molecules and their possible association with this proteoglycan molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Exocytosis of the 35S-labeled proteoglycan from the CNK8 cell was also stimulus specific, being 53% upon incubation with the K562 sensitive target, and 3% for the CEM-resistant target. The correlation of proteoglycan release with target cell susceptibility, coupled with the inhibition of proteoglycan release by monocional antibodies that block JTBI8 and CNK8 cytotoxicity indicates that specific NK effector cell receptors and target cell recognition structures are involved in triggering proteoglycan exocytosis (42). The ability to define one of the granule constituents, proteoglycan, exocytosed from the NK cell via receptor-mediated activation should enable the identification of other granule-associated molecules and their possible association with this proteoglycan molecule.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for a considerable time that PGs are components of the secretory granule of cytotoxic cells. In 1985 it was reported that NK cells contained a protease-resistant chondroitin sulfate PG species that was released upon incubation of the NK cells with target cells, and the possibility that these PGs are involved in the packaging of cytolytic granule compounds was discussed (16,17). Indeed, a subsequent report suggested that both perforin and granzyme A interacted with PGs at acidic pH, although the interaction with perforin with PGs was weakened at neutral pH (18).…”
mentioning
confidence: 99%
“…Recently, proteoglycans of the chondroitin sulfate A type have been identified in the granules of NK cells and shown to be released from cells during cytolysis (25,26). As shown here, proteoglycans may also be used as a granule marker for CTLL .…”
Section: Discussionmentioning
confidence: 81%
“…Proteoglycans of CTLL-R8 cell granules can also be visualized on polyacrylamide gels stained with Alcian Blue, which reveal several bands of different molecular masses (profile not shown here). Because proteoglycans have previously been speculated to exert a protective function during cell-mediated killing, tentatively through their binding to PFP/perforin released from cells (25,26), we tested the effects of heparin and chondroitin sulfate on the hemolytic activity mediated by PFP. Only heparin inhibited hemolysis at high concentrations (0.5 mg/ml), whereas chondroitin sulfate (and the three subtypes A, B, and C) produced no effect in the wide concentration range tested in our experiments.…”
Section: Discussionmentioning
confidence: 99%